2005
DOI: 10.1007/bf03023080
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based perioperative risk reduction

Abstract: HE purpose of this article is to examine the perioperative cardiac risk evidence and comment on the recommendations stemming from the evidence. We will assess the effect the evidence and the recommendations have had on practice.T Th he e d di il le em ma a Have the changes made to perioperative practice modified outcomes?Death is four times more common on the first day after surgery than the death rate in an age and risk adjusted population not having surgery.1 More than 50% of these deaths are a direct result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
(43 reference statements)
0
5
0
1
Order By: Relevance
“…Es recomendable suspender la metformina uno a dos días previos a la cirugía, especialmente en pacientes en diabéticos tipo 2 o con riesgo de hipoperfusión renal, hipoxia tisular y acumulación de lactato . Esta medida busca evitar la hipoglucemia reactiva dado que los pacientes que sufren de hipoglucemia tienen una mayor duración de la estancia y un aumento en la incidencia de complicaciones, especialmente la causada por hipoglicemiantes de tipo sulfonilureas 29,[37][38][39] . Si se presentan picos de hiperglucemia, estos se deben tratar con insulina de acción rápida por vía subcutánea 25,31 .…”
Section: Período Preoperatoriounclassified
“…Es recomendable suspender la metformina uno a dos días previos a la cirugía, especialmente en pacientes en diabéticos tipo 2 o con riesgo de hipoperfusión renal, hipoxia tisular y acumulación de lactato . Esta medida busca evitar la hipoglucemia reactiva dado que los pacientes que sufren de hipoglucemia tienen una mayor duración de la estancia y un aumento en la incidencia de complicaciones, especialmente la causada por hipoglicemiantes de tipo sulfonilureas 29,[37][38][39] . Si se presentan picos de hiperglucemia, estos se deben tratar con insulina de acción rápida por vía subcutánea 25,31 .…”
Section: Período Preoperatoriounclassified
“…13,21,22 Sulfonylureas have a potassium-channel-blocking effect that may interfere with myocardial ischemia preconditioning. 23,24 It has been shown that patients who are undergoing coronary infusions may provide better control and are likely to be more accepted by nursing staff. 6,13,33,34 Not only have studies shown that hypoglycemia or hyperglycemia may be detrimental, but increased BG variability may also play an important role with respect to complications and outcome.…”
Section: Preoperative Blood Glucose Effects On Intraoperative Carementioning
confidence: 99%
“…The perioperative use of β blockers has been advocated for patients at increased cardiac risk [51][52][53][54]. Nonetheless, the rationale for use of β blockers in diabetics before major noncardiac surgery was recently questioned in the Diabetic Postoperative Mortality and Morbidity (DIPOM) trial [55].…”
Section: Additional Therapiesmentioning
confidence: 99%